Self-Driven Success: Studi Kualitatif Motivasi Intrinsik Mahasiswa Edupreneur melalui Lensa Teori Determinasi Diri - Tnopo, Isfridus Tafin; Daeng, Sirilus Ugi; Utomo, Hanggara Budi (Universitas Negeri Malang, 2025)
The phenomenon of students engaging in entrepreneurship while undergoing higher education is growing, marking the emergence of a new identity as edupreneurs. This is influenced by various psychological factors that play a significant role in shaping entrepreneurial intentions and behaviors among university students. This study aims to explore in depth the intrinsic motivation of students in running a business through a phenomenological approach based on self-determination theory. Data were collected through in-depth interviews with three students who run different businesses, namely a fresh vegetable provider, a coffee shop, and a used clothing seller. Thematic analysis was conducted based on three fundamental psychological needs: autonomy, competence, and connectedness. The results show that students' intrinsic motivation is formed through the experience of running a business that provides freedom in making decisions, opportunities to develop skills, and support from the social environment. These findings reinforce the concept of self-determination theory that sustainable and meaningful motivation stems from the fulfillment of basic psychological needs. The contribution of this research is that it can broaden the understanding of the formation of student entrepreneurial behavior and the importance of the role of higher education in supporting the development of the intrinsic motivation of edupreneur students. AbstrakFenomena mahasiswa yang terlibat dalam dunia kewirausahaan sambil menjalani pendidikan tinggi semakin berkembang, menandai munculnya identitas baru sebagai edupreneur. Hal ini dipengaruhi oleh berbagai faktor psikologis yang memainkan peran penting dalam membentuk niat dan perilaku kewirausahaan di kalangan mahasiswa. Penelitian ini bertujuan untuk mengeksplorasi secara mendalam motivasi intrinsik mahasiswa dalam berwirausaha melalui pendekatan fenomenologi berdasar teori determinasi diri. Data dikumpulkan melalui wawancara mendalam terhadap tiga mahasiswa yang menjalankan usaha berbeda yaitu penyedia sayuran segar, penjual warung kopi, dan penjual pakaian bekas. Analisis tematik dilakukan berdasarkan tiga kebutuhan psikologis dasar yaitu otonomi, kompetensi, dan keterhubungan. Hasil penelitian menunjukkan bahwa motivasi intrinsik mahasiswa terbentuk melalui pengalaman menjalankan usaha yang memberikan kebebasan dalam mengambil keputusan, kesempatan untuk mengembangkan keterampilan, dan dukungan dari lingkungan sosial. Temuan ini memperkuat konsep teori determinasi diri bahwa motivasi yang berkelanjutan dan bermakna berakar dari pemenuhan kebutuhan psikologis dasar. Kontribusi penelitian ini adalah dapat memperluas pemahaman mengenai pembentukan perilaku kewirausahaan mahasiswa dan pentingnya peran pendidikan tinggi untuk mendukung pengembangan motivasi intrinsik mahasiswa edupreneur.